Effects of Diet and Water Monoglyceride and Acid Supplementation on Nursery Pig Performance - Ty H. Kim; Jason C. Woodworth; Mike D. Tokach; Joel M. DeRouchey; Robert D. Goodband; Katelyn N. Gaffield; Jordan T. Gebhardt; Ying Chen; Mark Whitney (Kansas Agricultural Experiment Station Research Reports, 2025)
A total of 2,520 pigs (PIC 337 × 1050, initially 11.5 ± 0.22 lb) were used in a 42-d study to determine the effects of dietary and water-based monoglyceride and acid supplementation on growth performance of nursery pigs. Pigs were weaned at approximately 20 d of age and randomly allotted to pens. Pens of pigs were blocked by initial BW and allotted to one of six treatments in a randomized complete block design with 30 pigs per pen and 14 pens per treatment across two rooms. Treatment diets were formulated in three phases and fed based on a feed budget. The six treatments were arranged in a 2 × 3 factorial with main effects of acidifier supplementation in water (Control or Protaq Bond 50) and feed (Control, Acitra G20C, or Acitra G20C and Entero-Nova 410C). Protaq Bond 50 is a blend of organic acids and monoglycerides applied to the water source through the water medicator included at a rate to reach a target water pH of 4.0. Acitra G20C, a blend of organic acids, was included at 0.3% in phase 1, 0.15% in phase 2, and 0% in phase 3. Entero-Nova 410C, a blend of monoglycerides, was included at 0.3% in phases 1 and 2, and 0.1% in phase 3. Pigs were weighed and feed disappearance was measured every 7 d to determine ADG, ADFI, and F/G. From d 0 to 7, pigs provided water with Protaq Bond 50 had increased (P < 0.001) ADG and improved (P < 0.001) F/G compared to pigs provided control water. Over the entire 42-d period, there were no differences (P > 0.10) in ADG or ADFI for water or feed treatments. There was a tendency (P = 0.098) for a main effect of diet on F/G, where pigs fed Acitra G20C had the lowest numerical F/G and pigs fed the control diet had the highest numerical F/G. For mortality, there was a tendency (P = 0.055) for a water × diet interaction, where diet did not affect mortality in pigs provided the control water; however, when provided Protaq Bond 50 in the water, pigs fed Acitra G20C had numerically lower mortality, while pigs fed Acitra G20C and Entero-Nova 410C had numerically higher mortality compared to pigs fed the control. There were no differences (P > 0.10) in removals or total removals and mortality. In summary, pigs receiving Protaq water had improved ADG and F/G compared to pigs on the control water in the first 7 d post-weaning. Pigs fed a blend of organic acids had numerically improved F/G compared to pigs fed the control, but there was no further benefit when both organic acids and monoglycerides were included in the diet. The addition of monoglycerides and other acidifiers in feed or water had no effect on overall ADG, ADFI, removals, or total removals and mortality.
Keywords: fecal dry matter; monoglycerides; nursery pigs; organic acid; water